2010
DOI: 10.1682/jrrd.2009.07.0088
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and entropy changes for back muscle fatigability following spinal stabilization exercises

Abstract: Abstract-The entropy of electromyography (EMG) signals suggests a possible tool for the clinical assessment of low back pain (LBP). However, a general physiological mechanism for entropy and pain and/or dysfunction following exercise intervention is still unknown. This comparative study investigated the differences between entropy levels of the EMG signals and the slope of median frequency (MF) based on power spectrum analysis in chronic LBP subjects after 4 weeks of spinal stabilization exercises (SSEs). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…However, it is necessary to determine www.intechopen.com whether the observed Shannon (information) entropy, as compared with MF, was able to differentiate fatigability of the thoracic and lumbar parts of the erector spinae muscle following the intervention. Previously, our lab investigated tools for evaluating back muscle fatigability after spinal stabilization exercises in participants with chronic LBP (Lee et al, 2010;Sung et al, 2005;Sung et al, 2008a;Sung et al, 2010). The results of our previous study indicated that Shannon entropy might be a valuable tool to measure the differences of outcomes following the exercise intervention.…”
Section: Sensitivity Of Surface Electromyography Analysismentioning
confidence: 89%
See 3 more Smart Citations
“…However, it is necessary to determine www.intechopen.com whether the observed Shannon (information) entropy, as compared with MF, was able to differentiate fatigability of the thoracic and lumbar parts of the erector spinae muscle following the intervention. Previously, our lab investigated tools for evaluating back muscle fatigability after spinal stabilization exercises in participants with chronic LBP (Lee et al, 2010;Sung et al, 2005;Sung et al, 2008a;Sung et al, 2010). The results of our previous study indicated that Shannon entropy might be a valuable tool to measure the differences of outcomes following the exercise intervention.…”
Section: Sensitivity Of Surface Electromyography Analysismentioning
confidence: 89%
“…As reported in our previous studies, the complexity of physiologic time series is a sensitive measure for muscle fatigability (Lee et al, 2010). However, it is necessary to determine www.intechopen.com whether the observed Shannon (information) entropy, as compared with MF, was able to differentiate fatigability of the thoracic and lumbar parts of the erector spinae muscle following the intervention.…”
Section: Sensitivity Of Surface Electromyography Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…This plateau value of S(t) was referred to as the entropy. The detailed entropy calculation process is fully described in previous studies [35,25]. Our previous data were partially used in this study in order to monitor the effects of the exercise intervention.…”
Section: Methodsmentioning
confidence: 99%